Aplikasi campuran serbuk kayu pinus dan fipronil sebagai umpan rayap tanah Macrotermes gilvus (Hagen) (Isoptera: Termitidae) di Bandung - Amran Amran; Intan Ahmad; Ramadhani Eka Putra; Eko Kuswanto (Jurnal Entomologi Indonesia, 2015)
In this study, termite bait comprising pinewood of sawdust and a slow action insecticide, fipronil, was made and applied to control subterranean termite Macrotermes gilvus (Hagen) (Isoptera: Termitidae) in Bandung. Colony size was measured using capture-mark-release-recapture prior to the bait application, along with the measurement of wood consumption at each station.  Colony foraging populations at all stations were estimated to be 77,951 termites, with mean wood consumption rates ranging from 0.02 to 6.16 g/station/day. Observation at 18 stations installed with bait consisted of 40 ppm fipronil mixed with pinewood sawdust showed that number of foraging activity termites was effectively reduced in 40 days. It is concluded that fipronil-treated pinewood sawdust bait is effective in controlling the population of foraging M. gilvus workers in 40 days.